The necessity of adjuvant radiotherapy for locally advanced gastric cancer in China - Yang, Yongqiang; Xing, Pengfei; Zhou, Ning; Wu, Yongyou; Zhang, Liyuan; Tian, Ye (Translational Cancer Research; Vol 8, No 2 (April 30, 2019): Translational Cancer Research, 2019)
Nearly 50% of the new gastric cancer cases and gastric cancer-related deaths worldwide occur in China. Although the Guidelines for the Diagnosis and Treatment of Gastric Cancer from the National Health Commission of the People’s Republic of China have explicitly emphasized the necessity of adjuvant chemoradiation for gastric cancer, few clinical institutions in China routinely administer postoperative adjuvant radiation therapy in patients with gastric cancer. At present, radical resection combined with postoperative chemotherapy alone is the most common treatment for locally advanced gastric cancer in China. However, several phase III prospective randomized controlled trials in Europe have shown that adjuvant chemotherapy alone after a radical resection does not improve the disease-free survival (DFS) or overall survival (OS) of patients with gastric cancer. As in Japan and South Korea, D2 radical resection is the recommended surgical approach for gastric cancer in China. However, several studies have shown that the rate of D2 resection in the treatment of gastric cancer patients in China is low. Nearly 50% of patients undergo a D0-1 radical resection, even at the leading gastric cancer centers in China. The results of the INT-0116 study in the US suggest that gastric cancer patients who undergo a D0-1 radical resection and have stage T3-4 or N+ disease should receive concurrent postoperative radiation therapy and chemotherapy. In conclusion, many patients with gastric cancer do not receive a standard D2 resection in China. As a result, it is important to consider postoperative adjuvant chemoradiation especially in those patients who undergo a D0-1 radical resection.